Behavioral Economics and the Value of a Statistical Life - Thomas J. Kniesner (Institute of Labor Economics (IZA), 2019)
There are many possible connections between VSL and behavioral economics. A list of topics includes endowment effects, risk salience, ambiguity aversion, present bias, reference groups, reference points, and experienced versus decision utilities. There are also nudges that connect to estimating or using VSL in government decisions and cousins of behavioral economic research including interpersonal heterogeneity, experiments, neuroeconomics, and beauty or personal attractiveness. Current evidence suggests that VSL and behavioral economics best connect via (1) possible multi-attribute reference group effects and (2) a possible distinction between decision utility and experienced utility.
Keywords: D61; D91; J17; J31; 330; VSL; behavioral economics; WTP; WTA; reference dependence; benefit-cost analysis; nudge; internality